2010
DOI: 10.1142/s0218625x10014193
|View full text |Cite
|
Sign up to set email alerts
|

GROWTH MODE OF Sn ON A AU(111) SUBSTRATE

Abstract: Atomistic simulations of low coverage Sn growth on Au(111) using the Bozzolo-Ferrante-Smith (BFS) method for alloys are presented. Simulated annealing and atom-by-atom analysis of the energetics explains the close competition between the experimentally observed surface alloying and layer-by-layer growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…23 The Au-Sn alloys have been reported in literature to be non-toxic soldering materials with good bonding characteristics and these are widely used in advanced electronic circuits as well as in optoelectronic devices. 19,24,25 Theoretical studies 26,27 also support surface alloying in Au-Sn, for example, Meier and Castellani 26 show that at 0.5 ML coverage, half of the Au atoms of the top layer are displaced forming a plane in between the adsorbed Sn atoms and the Au top layer atoms. This result supports an earlier Monte Carlo based theoretical study that showed a close competition between surface alloying and layer-by-layer growth at room temperature.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…23 The Au-Sn alloys have been reported in literature to be non-toxic soldering materials with good bonding characteristics and these are widely used in advanced electronic circuits as well as in optoelectronic devices. 19,24,25 Theoretical studies 26,27 also support surface alloying in Au-Sn, for example, Meier and Castellani 26 show that at 0.5 ML coverage, half of the Au atoms of the top layer are displaced forming a plane in between the adsorbed Sn atoms and the Au top layer atoms. This result supports an earlier Monte Carlo based theoretical study that showed a close competition between surface alloying and layer-by-layer growth at room temperature.…”
Section: Introductionmentioning
confidence: 98%
“…This result supports an earlier Monte Carlo based theoretical study that showed a close competition between surface alloying and layer-by-layer growth at room temperature. 27 In this paper, we present a study of the electronic structure of Au-Sn intermetallic compounds grown on Au(111) using x-ray photoelectron spectroscopy (XPS), LEED, and angle resolved photoemission spectroscopy (ARPES). An analysis of the XPS core-level spectra shows that AuSn grows on Au(111) at room temperature, while high temperature treatment forms Au rich phases, for example, Au 5 Sn.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to reserving or tuning the electronic properties of stanene, another critical issue is the preparation of large-scale and high-quality stanene films . Even though tin tends to form alloys with many metals, ,, including Cu, Ag, and Au, , these alloy-terminated surfaces can serve as the template to grow stanene, as we show below. Many elegant examples, such as the growth of antimonene on alloyed Cu 2 Sb and Ag 2 Sb, , the segregation growth of germanene through Ag layers on Ge(111), and the generation of planar silicene through Au thin films on Si(111), have demonstrated the critical role of surface alloys in the formation of 2D materials.…”
mentioning
confidence: 99%
“…On the basis of previous studies on the growth of Sn on Au(111) in which the substrate temperature determined the structures of as-grown atomic layers, ,,,, we first investigate the Sn films directly deposited on freshly prepared Au 2 Sn­(111) with the same deposition time and evaporation rate under different substrate temperatures, as summarized in Figure . At low substrate temperature (330 K), the surface is fully covered by Sn tetramers and nanometer-sized aggregates (Figure a).…”
mentioning
confidence: 99%